THE EFFECT OF TASK SPECIFIC TRAINING BASED ON COCONTRACTION WITH EXTERNAL CLUE FOR FUNCTIONAL ABILITY ON OSTEOARTHRITIS KNEE: SINGLE CASE REPORT - Zhulfahmi, Moch. Rizki; Perdana, Suryo Saputra; Prasetijo, Dedy Herman (Academic Physiotherapy Conference Proceeding, 2021)
Introduction: Osteoarthritis Knee is a symptom that often comes in elderly people, a chronic progressive condition that causes movement disorders and interferes with activities. The intervention is task specific training. Task specific training is an effective rehabilitation program for balance, walking speed and reducing pain in OA. External Clue is the therapist providing information about the performance of motor skills so that the patient can get feedback from the patient himself. Case Presentation: Mrs. S is 68 years old. The patient has a height of 155 cm and a weight of 70 kg. Mrs. S works as a housewife. The patient had this complaint several years ago. There is no history of illness in the family. Supporting data in the form of X-ray with the interpretation of knee osteoarthritis grade 2. The patient also suffered from mild deformity of the foot towards varus, the presence of crepitus, but the patient did not have local oedema, no pes anserinus bursitis and no joint tendeness. Management and Outcome: The patient underwent treatment consisting of Task Specific Training based on Co-Contraction with External Clue. The patient is instructed to contract the muscles while walking. Coactivation occurs when the flexor muscles are active during the moment of extension. (External Clue) is the therapist providing additional information about the performance of motor skills so that the patient can get feedback from the patient himself. The osteoarthritis instrument used is WOMAC (Western Ontario and McMaster Universities) pain T1: 8 to T7: 3, stiffness T1:2 to T7: 2, physical function T1: 24 to T7: 7. Discussion: The subjects of this study have typical symptoms of osteoarthritis of the knee, so there is no need for additional examinations to diagnose knee osteoarthritis in these subjects. This is supported by international guidelines which state that individuals with signs such as individuals aged >45 years, pain when doing activities, and morning stiffness <30 minutes can be directly diagnosed with knee osteoarthritis. Task specific has the concept of muscle cocontraction where (simultaneous coordinated activity of agonist and antagonist muscles) is considered as the main mechanism for joint stabilization, load distribution, and control of movement during gait. Muscle co-contraction for activities of daily living (ADL) can be combined with different muscles. It is therefore important to understand muscle co-activation strategies across different ADLs and across different muscle combinations. Conclusion: Obtained an increase in functional ability in patients with knee osteoarthritis.